Uji in vitro patogenisitas Beauveria bassiana terhadap larva ulat pucuk Strepsicrates rhothia hama tanaman jambu kristal - Asya, Dinda Putri; Hasibuan, Rosma; Solikhin, Solikhin; Fitriana, Yuyun (Jurnal Proteksi Agrikultura, 2025)
The purpose of this study was to find out the growth of Beauveria bassiana fungal colonies in vitro on PSA media and to find out the pathogenicity of B. bassiana fungus against Strepsicrates rhothia larvae. The experiment was conducted using a Randomized Complete Block Design (RCBD), comprising five treatment levels of B. bassiana spore density: 7.1 × 10⁴, 7.1 × 10⁵, 7.1 × 10⁶, 7.1 × 10⁷ conidia/mL, and without B. bassiana as control. Each treatment was replicated three times. The results showed that the average growth of B. bassiana fungus two weeks after inoculation was 3.9 cm. The number of spores of B. bassiana fungus at dilutions of 10-1, 10-2, 10-3, and 10-4 was 7.1 x 107, 7.1 x106, 7.1 x 105, and 7.1x 104 conidia/mL, respectively. After 24 hours of incubation, the viability of B. bassiana spores reached 86.04% and at a spore concentration of 7.1 × 10⁷ conidia/mL, B. bassiana resulting in 100% mortality of S. rhothia larvae.